Neutrophil Lymphocyte Ratio and Mortality in Patients with Acute Limb Ischemia - Hapsari, Putie; Djajakusumah, Teguh Marfen; Nugroho, Hendri Bayu (Majalah Kedokteran Bandung, 2025)
Acute Limb Ischemia (ALI) is a sudden decrease in limb perfusion with a potential of limb loss and is an indication for immediate vascular intervention. Apart from reducing the quality of life, the mortality rate in ALI is reported to be high, i.e., around 40%. Neutrophil Lymphocyte Ratio (NLR) can be used to reflect the inflammatory process in this condition. This study aimed to assess the correlation of NLR to mortality rate in ALI Rutherford Category III patients treated in Dr. Hasan Sadikin General Hospital Bandung, Indonesia. This was a cross-sectional analytical observative retrospective study on data collected from medical records of ALI Rutherford Category III patients treated in the hospital from 2019 to 2022. Sampling was performed consecutively and data were processed using the SPSS with univariate analysis and bivariate analysis using Kendall's tau b analysis test. Results demonstrated that of a total of 46 patients, the majority were female patients (n=31) and 28 patients died. The mean NLR levels in patients who survived was 5.8, in contrast with 9.7 observed among those who died. The statistical test results showed a significant correlation between the NLR and mortality rate of ALI Rutherford category III patients (p